FONTES DE RESISTÊNCIA À MANCHA-ANGULAR DO FEJOEIRO EM MINHAS GERAIS - NIETSCHE, SILVIA; Borém, Aluizio; Carvalho, Geraldo Assis de; Paula Júnior, Trazilbo José de; Barros, Everaldo Gonçalves de; Moreira, Maurílio Alves (Revista Ceres, 2015)
-